2018
DOI: 10.3390/molecules23020397
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Bioconversion of Azelaic Acid to Its Derivatives by Response Surface Methodology

Abstract: Azelaic acid (AzA) and its derivatives have been known to be effective in the treatment of acne and various cutaneous hyperpigmentary disorders. The esterification of azelaic acid with lauryl alcohol (LA) to produce dilaurylazelate using immobilized lipase B from Candida antarctica (Novozym 435) is reported. Response surface methodology was selected to optimize the reaction conditions. A well-fitting quadratic polynomial regression model for the acid conversion was established with regards to several parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…A positive sign in the equation showed a synergistic effect. A negative sign indicated as an antagonistic effect [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A positive sign in the equation showed a synergistic effect. A negative sign indicated as an antagonistic effect [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The important influence of efficient variables on the hydroxyl value was demonstrated by Pareto analysis as shown in Figure 7 . The Pareto analysis expresses the influence of each variable, in percentages, on the response in relation to the coefficient of the coded variable in Equation (3) [ 33 , 47 ]. The pareto analysis showed that variable B (catalyst) gave the most important influence on the response (hydroxyl value) at 45.89% followed by variable A (mole ratio of EMO:Glycerol) at 37.61% and the interaction between A and B at 6.98%.…”
Section: Resultsmentioning
confidence: 99%
“…268 Azelaic acid was diesterified with lauric alcohol using N435 and used as a bacteria growth inhibitor. 269 Another paper shows that methyl caffeate production via esterification catalyzed by N435 was improved via a microfluidic strategy in a continuous-flow reactor (yields surpassed 98% in 2.5 h). 270 N435 was also used in the esterification of oleic acid and kojic acid in a stirred tank reactor with a yield near 43%.…”
Section: Lewatit Vp Oc 1600mentioning
confidence: 99%
“…The derivates of the azelaic acid are characterized by better solubility and require less dosage than acid form. The synthesis by esterification of azelaic acid with lauryl alcohol, catalyzed by CAL-B (Novozym 435) was carried out by Khairudin et al The high conversion (> 95%) was achieved with a small amount of enzyme [19].…”
Section: Lipase B From Candida Antarctica (Cal-b) -Applicationmentioning
confidence: 99%